Effectiveness of Ramp Safety Awareness Training to Improve On-the-Job Training Students Safety Awareness - I Gusti Agung Ayu Mas Oka; Retno Sawitri Wulandari; Fitri Masito (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The high risk at airports, especially in the apron and ramp areas, required personnel awareness of safety in those areas. This study was conducted to evaluate the Ramp Safety Awareness (RSA) training program for On-The-Job Training (OJT) students, in order to enhance safety awareness in the ramp area. This study employed an evaluation model developed by Robert E. Stake, known as the Countenance Model. The Stake evaluation model comprises three stages: antecedent, transaction, and output. The evaluation results at the transaction and output stages demonstrated that the RSA training was effective. The training process proceeded smoothly and successfully met its learning objectives. Additionally, the RSA training was found to be extremely beneficial for OJT students in carrying out their duties during the program. Meanwhile, the evaluation results at the antecedent stage revealed that certain improvements were necessary. First, it was essential to revise the OJT guidelines to establish a solid legal foundation for RSA training. Second, program planning had to include RSA training for OJT students as part of the annual program planning at least one year prior to the training's implementation. Finally, there was a need to create a three-year internship program for instructors specializing in aviation safety.